Kurumsal Performans Karnesi Ölçümü: Üçüncü Basamak Sağlık Kurumlarında Bir Uygulama - Korkmaz, Oya (Muş Alparslan Üniversitesi, 2018)
In order to draw attention to the potential benefits of Balanced Scorecard and to make it available to hospitalmanagers, Balanced Scorecards were applied to a tertiary health care facilityin 2007, 2008 and 2009 and the following results were obtained. According tothe results obtained, total corporate performance was measured as 54.63% in2007, 62.48% in 2008 and 63.32% in 2009. In addition, the performances of thesub-dimensions of the Balanced Scorecard have also been determined for thespecified years. According to the result obtained, suggestions were made tomaintain the good performance and to improve the poor performance.

KurumsalPerformans Karnesinin (Balanced Scorecard) potansiyel faydasına dikkat çekmekve hastane yöneticilerinin kullanımına sunmak amıyla yapılan bu çalışmadaüçüncü basamak bir sağlık kuruluşuna 2007, 2008 ve 2009 yılları itibariyleKurumsal Performans Karnesi uygulanmış ve şu sonuçlar elde edilmiştir. Elde edilen sonuçlara göre, toplam kurumsalperformans 2007 yılında %54.63, 2008 yılında %62.48 ve 2009 yılında ise %63.32olarak ölçülmüştür. Ayrıca belirtilen yıllar itibariyle kurumsal performanskarnesinin alt boyutlarının performansları da tespit edilmiştir. Çıkan sonucagöre iyi performansın korunması, kötü performansın ise iyileştirilmesi yönündeönerilerde bulunulmuştur.
Institutional Balanced Scorecard Measurement: An Application in Tertiary Health Care Services
anemon
Keywords: Organizational Performance; Institutional Balanced Scorecard; Zonguldak Bülent Ecevit University Application and Research Hospital; Örgütsel Performans; Kurumsal Performans Karnesi; Zonguldak Bülent Ecevit Üniversitesi Uygulama ve Araştırma Hastanesi